Impaired removal of Vβ8+ lymphocytes aggravates colitis in mice deficient for B cell lymphoma‐2‐interacting mediator of cell death (Bim). (6th August 2013) - Leucht, K.; Caj, M.; Fried, M.; Rogler, G.; Hausmann, M.
Summary: We investigated the role of B cell lymphoma (BCL)‐2‐interacting mediator of cell death (Bim) for lymphocyte homeostasis in intestinal mucosa. Lymphocytes lacking Bim are refractory to apoptosis. Chronic colitis was induced in Bim ‐deficient mice ( Bim –/– ) with dextran sulphate sodium (DSS). Weight loss and colonoscopic score were increased significantly in Bim –/– mice compared to wild‐type mice. As Bim is induced for the killing of autoreactive cells we determined the role of Bim in the regulation of lymphocyte survival at mucosal sites. Upon chronic dextran sulphate sodium (DSS)‐induced colitis, Bim –/– animals exhibited an increased infiltrate of lymphocytes into the mucosa compared to wild‐type mice. The number of autoreactive T cell receptor (TCR) Vβ8 + lymphocytes was significantly higher in Bim –/– mice compared to wild‐type controls. Impaired removal of autoreactive lymphocytes in Bim –/– mice upon chronic DSS‐induced colitis may therefore contribute to aggravated mucosal inflammation.